Repeated muscle glycogen supercompensation with four days' recovery between exhaustive exercise. Issue 8 (August 2019) - Doering, Thomas M.; Cox, Gregory R.; Areta, José L.; Coffey, Vernon G.
Abstract: Objectives: To determine if a 4 d period of high carbohydrate intake can supercompensate muscle glycogen and exercise work capacity on back-to-back occasions. Design: Seven trained cyclists (6 male, VO2 peak: 57 ± 4 mL kg −1  min −1 ) completed a 9-d experimental period, consisting of three intermittent exhaustive cycling trials on days 1 (trial 1), 5 (trial 2) and 9 (trial 3). Following trial 1 cyclists were fed a high carbohydrate diet (˜10 g kg −1  day −1 ) for eight days to assess their capacity to repeatedly supercompensate muscle glycogen with 4 d recovery. Methods: A resting muscle biopsy was obtained prior to each trial consisting of 2 min work intervals (90–60% peak power output) interspersed with 2 min recovery (40% peak power output) repeated until exhaustion. Each 72-h period between trial days included two days of low volume cycling and a rest day. Resting muscle glycogen and total work completed was determined for each trial day. Results: Baseline muscle glycogen on day 1 (583.6 ± 111.0 mmol kg −1 dry mass) was supercompensated on day 5 (835.1 ± 112.8 mmol kg −1 dry mass; p = 0.04, d = 2.25) and again on day 9 (848.3 ± 111.4 mmol kg −1 dry mass; p = 0.01, d = 2.38). Total cycling work capacity increased from trial 1 to trial 2 (+8.7 ± 5.4 kJ kg −1 ; p = 0.01; d = 1.41); a large effect was observed in trial 3 compared to trial 1 (+6.4 ± 6.8 kJ kg −1 ; p = 0.10; d = 1.10). Conclusions: A 4 d high carbohydrate feeding strategy is sufficient to repeatedly supercompensate muscle glycogen content following exhaustive exercise and results in enhanced work capacity.